The effect of shade during summer and confinement area during winter on milk production, milk composition, physiological responses and behaviour of Friesian cows in a temperate climate - Muller, C. J. C (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosck, 1991.